A century of pluralistic ignorance: what we have learned about its origins, forms, and consequences - Miller, Dale T. (Frontiers in Social Psychology, 2023)
The concept of pluralistic ignorance was introduced a century ago by social psychologist, Floyd Allport. Since then, it has been broadly applied in the social sciences, including psychology, sociology, political science, and economics. Pluralistic ignorance is a situation in which group members systematically misperceive their peers' attitudes, feelings, and private behaviors. This paper reviews the range of phenomena that pluralistic ignorance has been invoked to explain, the different accounts that have been offered for its emergence, and the various techniques that have been employed to dispel it. It distinguishes between micro and macro variants of pluralistic ignorance and discusses the challenges involved in generating a theory that encompasses both variants.The concept of pluralistic ignorance has a long past but a short history, to use Hermann Ebbinghaus ' (1908) phrase. Floyd Allport coined the term one hundred years ago (Allport, 1924; Katz and Allport, 1931). For many years thereafter it received scant theoretical or empirical attention, attested to by the term's meager 13 entries in PsychInfo's data base in the 5 decades following its coinage, a number surpassed in the year 2022 alone. Pluralistic ignorance is a situation where the plurality (group) is ignorant of (misperceives) itself-its beliefs, perceptions, and practices. The group experiencing pluralistic ignorance is not actually ignorant in the sense of lacking knowledge of where it stands but is rather mistaken as to where it stands (O'Gorman, 1986). A more descriptive, if less catchy, term might be collective misperception (Grant, O'Neil, and Stephens, 2009; Miller & Prentice, 1994). Despite being a common citation for pluralistic ignorance, Allport's 1924 Social Psychology did not mention the term; that awaited his 1931 book with his student, Daniel Katz (Katz and Allport, 1931). What Allport did discuss in his earlier tome was the "illusion of universality of opinions." He traced this "illusion", which he later renamed pluralistic ignorance, to two facts: 1) social life depends on individuals having knowledge of their peers' habitual feelings and practices, and 2) individuals must infer this knowledge from limited and thus potentially misleading information.